P1NP and β-CTX-1 Responses to a Prolonged, Continuous Running Bout in Young Healthy Adult Males: A Systematic Review with Individual Participant Data Meta-analysis - Rita Civil; Eimear Dolan; Paul A. Swinton; Lívia Santos; Ian Varley; Philip J. Atherton; Kirsty J. Elliott-Sale; Craig Sale (SpringerOpen, 2023)
Abstract Background Circulating biomarkers of bone formation and resorption are widely used in exercise metabolism research, but their responses to exercise are not clear. This study aimed to quantify group responses and inter-individual variability of P1NP and β-CTX-1 after prolonged, continuous running (60-120 min at 65-75% V̇O2max) in young healthy adult males using individual participant data (IPD) meta-analysis. Methods The protocol was designed following PRISMA-IPD guidelines and was pre-registered on the Open Science Framework prior to implementation ( https://osf.io/y69nd ). Changes in P1NP and β-CTX-1 relative to baseline were measured during, immediately after, and in the hours and days following exercise. Typical hourly and daily variations were estimated from P1NP and β-CTX-1 changes relative to baseline in non-exercise (control) conditions. Group responses and inter-individual variability were quantified with estimates of the mean and standard deviation of the difference, and the proportion of participants exhibiting an increased response. Models were conducted within a Bayesian framework with random intercepts to account for systematic variation across studies. Results P1NP levels increased during and immediately after running, when the proportion of response was close to 100% (75% CrI: 99 to 100%). P1NP levels returned to baseline levels within 1 h and over the next 4 days, showing comparable mean and standard deviation of the difference with typical hourly (0.1 ± 7.6 ng·mL−1) and daily (− 0.4 ± 5.7 ng·mL−1) variation values. β-CTX-1 levels decreased during and up to 4 h after running with distributions comparable to typical hourly variation (− 0.13 ± 0.11 ng·mL−1). There was no evidence of changes in β-CTX-1 levels during the 4 days after the running bout, when distributions were also similar between the running data and typical daily variation (− 0.03 ± 0.10 ng·mL−1). Conclusion Transient increases in P1NP were likely biological artefacts (e.g., connective tissue leakage) and not reflective of bone formation. Comparable small decreases in β-CTX-1 identified in both control and running data, suggested that these changes were due to the markers' circadian rhythm and not the running intervention. Hence, prolonged continuous treadmill running did not elicit bone responses, as determined by P1NP and β-CTX-1, in this population.